The Impact Of Physical Education On Psychological And Social Development - Karimov Bekzod Boyqobilovich (Euro Asian Journal Publishing, 2025)
This article analyzes the physical and biological foundations of the adaptation process in sports. The study examined the adaptive mechanisms of the cardiovascular and respiratory systems, energy metabolism, and the physiological-biochemical processes associated with stress response. The findings provided a basis for developing practical recommendations to improve athletes' adaptation during training. The study demonstrated that the body's adaptive capacities increase in proportion to the intensity and duration of training, which plays a crucial role in ensuring overall performance and maintaining athletes' health
Keywords: Adaptation in sports; Physical adaptation; Biological mechanisms